The Impact of the Industrial Internet on the New Quality Productivity of Distribution Enterprises - Gao, Yuandong; Zhang, Xiaohui; Tang, Jian (Journal of Global Economy, Business and Finance, 2026)
This study empirically investigates the impact of industrial internet on the new quality productivity of Chinese distribution enterprises using PSM-DID methods and panel data from 2013 to 2023. Results reveal a positive and robust effect of industrial internet on new quality productivity, with significant heterogeneity across property rights and regions—non-state-owned enterprises and western-region firms exhibit stronger responses. Mechanism analysis shows that industrial internet enhances technological innovation and data assets, thereby promoting new quality productivity. Policy implications include prioritizing new infrastructure development, implementing tiered industrial internet initiatives, and accelerating digital transformation in distribution enterprises.